(untitled) (Unilorin Journal of Lifelong Education, 2023)
This study investigated the effect of inside-outside circle instructional strategy on pupils’ academic achievement in mathematics in Ilorin West Local Government Area of Kwara State. Pretest post-test control group quasi-experimental research design was adopted. A total of 74 pupils from two public primary schools were involved in the study. One validated and reliably tested research instrument titled ‘Mathematics Achievement Test’ (MAT) was used. The reliability index of MAT (r = 0.74) was determined using test retest method. Three hypotheses were formulated and tested with Analysis of Covariance (ANCOVA). The findings of the study revealed that treatment had significant effect on pupils’ academic achievement in mathematics (F (1; 69) = 248.743, P < 0.05). However, gender (F (1; 69)=1.325; P > 0.05) did not have significant effect on pupils’ academic achievement in mathematics. And finally, the interaction of treatment and gender did not have any significant effect on pupils’ academic performance (F (1; 69) = .603; P > 0.05). Based on the findings, it was concluded that insideoutside circle instructional strategy can improve academic achievement of pupils in mathematics. Based on the conclusion, it was recommended that teachers should be trained on inside-outside circle instructional strategy and also be encouraged to use it.